2015
DOI: 10.1186/s12957-015-0630-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative photodynamic therapy as a new adjuvant treatment after robot-assisted salvage surgery of recurrent squamous cell carcinoma of the base of tongue

Abstract: BackgroundFor patients who remain with involved resection margins after transoral robot-assisted salvage surgery (TORS) for recurrent squamous cell carcinoma (SCC) at the base of tongue (BOT) following primary (chemo)radiotherapy, further adjuvant treatment options are very limited. We want to report on our preliminary experience with a new adjuvant strategy using postoperative temoporfin-mediated photodynamic therapy for this indication.MethodsTwo patients with recurrent SCC after primary (chemo)radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Adjuvant RT and CRT were administered in 4 (13.3%) and 2 (6.7%) salvage patients, respectively. Two other salvage patients (6.7%) underwent salvage surgery (TLM in one case and total laryngectomy in one case), and two other patients (6.7%) were treated with postoperative PDT because of involved resection margins after TORS procedure for recurrent SCC of the base of tongue after primary RT or CRT ( 22 ). Detailed data on neck dissection and adjuvant strategy for both the up-front and salvage groups are depicted in Tables 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant RT and CRT were administered in 4 (13.3%) and 2 (6.7%) salvage patients, respectively. Two other salvage patients (6.7%) underwent salvage surgery (TLM in one case and total laryngectomy in one case), and two other patients (6.7%) were treated with postoperative PDT because of involved resection margins after TORS procedure for recurrent SCC of the base of tongue after primary RT or CRT ( 22 ). Detailed data on neck dissection and adjuvant strategy for both the up-front and salvage groups are depicted in Tables 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to CT or RT, PDT often proves to be an effective, safe alternative with lower morbidity as can be seen in the trials discussed earlier. When PDT is used as salvage treatment after failed RCT, often cases of CR are reported indicating PDT at times is even more effective [ 167 , 168 , 211 ]. Together with the significantly lower morbidity of PDT and the possibility of combining it with RT and CT, this suggests PDT should be considered as a viable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report describes a small but impressive study investigating the use of mTHPC-PDT for the treatment of recurrent SCC of the base of tongue after salvage surgery following (chemo-) radiation failure. The two patients treated were disease free after 24 and 42 months follow-up [ 211 ]. mTHPC-PDT has also been shown to be a safe adjuvant therapy for recurrent malignant tumors of the paranasal sinuses and recurrent sino-nasal skull base tumors [ 212 , 213 ].…”
Section: Pdt In Clinical Trialsmentioning
confidence: 99%
“…The combined strategy can be conducted in different procedures: neoadjuvant PDT can efficiently destroy malignant tissues, thereby enhancing resectability or reducing the required resection extent 106 ; intraoperative PDT denotes the irradiation of the resection cavity with a proper wavelength during or after surgery 107 ; and postoperative PDT is conducted after suture of the incision. 108 The clinical data suggested that a combined strategy could more beneficial to patients with cancer than surgery alone. Neoadjuvant PDT along with chemotherapy has been shown to be effective and safe to facilitate the conversion of surgical candidates in locally advanced non-small cell lung cancer.…”
Section: The Combination Of Fgs With Pdtmentioning
confidence: 99%